The neuroprotective effect of melatonin in glutamate excitotoxicity of R28 cells and mouse retinal ganglion cells - Wang, Chao; An, Yaqiong; Xia, Zhaohua; Zhou, Xuezhi; Li, Haibo; Song, Shuang; Ding, Lexi; Xia, Xiaobo (Frontiers in Endocrinology, 2022)
Glaucoma is the leading cause of irreversible blindness. The progressive degeneration of retinal ganglion cells (RGCs) is the major characteristic of glaucoma. Even though the control of intraocular pressure could delay the loss of RGCs, current clinical treatments cannot protect them directly. The overactivation of N-methyl-D-aspartic acid (NMDA) receptors by excess glutamate (Glu) is among the important mechanisms of RGC death in glaucoma progression. Melatonin (MT) is an indole neuroendocrine hormone mainly secreted by the pineal gland. This study aimed to investigate the therapeutic effect of MT on glutamate excitotoxicity of mouse RGCs and R28 cells. The Glu-induced R28 cell excitotoxicity model and NMDA-induced retinal injury model were established. MT was applied to R28 cells and the vitreous cavity of mice by intravitreal injection. Cell counting kit-8 assay and propidium iodide/Hoechst were performed to evaluate cell viability. Reactive oxygen species and glutathione synthesis assays were used to detect the oxidative stress state of R28 cells. Retina immunofluorescence and hematoxylin and eosin staining were applied to assess RGC counts and retinal structure. Flash visual-evoked potential was performed to evaluate visual function in mice. RNA sequencing of the retina was performed to explore the underlying mechanisms of MT protection. Our results found that MT treatment could successfully protect R28 cells from Glu excitotoxicity and decrease reactive oxygen species. Also, MT rescued RGCs from NMDA-induced injury and protected visual function in mice. This study enriches the indications of MT in the treatment of glaucoma, providing practical research ideas for its comprehensive prevention and treatment.